New orchids in the flora of Vietnam IX (Orchidaceae: Orchidoideae, tribes Cranichideae and Orchideae) - Averyanov, Leonid V.; Nguyen, van Canh; Le, Tuan Anh; Vuong, Truong Ba; Nuraliev, Maxim S.; Maisak, Tatiana V.; Yudova, Daria A.; Nguyen, Cuong Huu; Nong, Duy Van (Phytotaxa, 2024)
The paper presents new data on the orchid diversity of Vietnam obtained mainly during the fieldwork of 2020–2023, as well as a result of investigation of the herbarium collections of Russia and Vietnam. It includes two species new to science, Bidoupia micrantha and Hylophila vietnamensis, and three species new to the native flora of Vietnam, i.e. Diphylax urceolata, Disperis neilgherrensis, and Habenaria siamensis. Three genera, Diphylax, Disperis and Hylophila, are reported here for the flora of Vietnam for the first time. In addition, a newly naturalized species Cynorkis fastigiata is documented, which originates from the Comoros, Madagascar, the Seychelles, and the Mascarenes. For each of the studied species, its type, relevant synonyms, studied specimens, ecology and phenology (within Vietnam), distribution, preliminarily assessed conservation status, brief taxonomic notes and illustrations are provided. For the newly described taxa, morphological descriptions and notes on etymology are additionally included.